Structural, transport and optical properties of (La0.6Pr0.4)0.65Ca0.35MnO3 nanocrystals: a wide band-gap magnetic semiconductor. Issue 7 (21st February 2015) - Kumar, Satyam; Dwivedi, G. D.; Kumar, Shiv; Mathur, R. B.; Saxena, U.; Ghosh, A. K.; Joshi, Amish G.; Yang, H. D.; Chatterjee, Sandip
<x xml:space="preserve">Abstract</x> Resistivity vs. temperature and valence band spectra of (La0.6Pr0.4)0.65Ca0.35MnO3 nanoparticles have been shown in figures. This figure clearly shows the hybridization of Mn3d(t2g) and O2p states.